GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU OPERATOR DEPOT SERTA UJI MIKROBIOLOGI AIR MINUM DI WILAYAH KERJA UPTD PUSKESMAS PUNGGELAN 2 TAHUN 2025 - Sri Nuraeni; Dwi Atin Faidah (Jurnal Ilmiah Medsains, 2025)
Refill Drinking Water Depots (DAM) are one of the main sources of drinking water for the community due to their practicality and affordability. However, the quality of the refill water produced by DAMs remains a concern, particularly in relation to microbiological contamination such as Escherichia coli and Coliform, which can pose health risks. An inspection of DAMs in the working area of UPTD Puskesmas Punggelan 2 in January 2025 found Coliform bacteria in two DAMs, indicating suboptimal implementation of hygiene and sanitation principles. This study aims to describe the knowledge, attitudes, and practices of DAM operators, as well as to assess the microbiological quality of drinking water in the working area of UPTD Puskesmas Punggelan 2. This research was conducted in May–June 2025. The study is descriptive in nature and used a cross-sectional approach through interviews and observations, with data collection instruments in the form of questionnaires and checklists. The subjects of the study were all operators and DAMs within the scope of UPTD Puskesmas Punggelan 2. The results showed that 57.1% of operators had moderate knowledge, 71.4% displayed positive attitudes, but only 42.9% demonstrated hygienic practices. Microbiological test results revealed that two depots were still contaminated with Coliform and E. coli bacteria. The findings indicate that Coliform and E. coli contamination is not directly related to the operators’ knowledge and behavior. There is a need to improve hygiene and sanitation training, provide regular supervision from the Health Center and Health Department, and implement strict monitoring of DAM operational practices.